Systematic revision of the Parvoscincus decipiens (Boulenger, 1894) complex of Philippine forest skinks (Squamata: Scincidae: Lygosominae) with descriptions of seven new species - Linkem, Charles W.; Brown, Rafe M. (Zootaxa, 2013)
Analysis of external morphological characters, color pattern, and DNA sequence data, plus consideration of biogeographical patterns, leads us to the hypothesis that the Parvoscincus decipiens complex of Philippine forest skinks consists of a minimum of eight highly divergent, phenotypically distinct, cohesive evolutionary lineages. We rectify this taxonomic underestimation of species diversity with formal descriptions of seven new species (P. abstrusus sp. nov., P. agtorum sp. nov., P. arvindiesmosi sp. nov., P. aurorus sp. nov., P. banahaoensis sp. nov., P. jimmymcguirei sp. nov., and P. palaliensis sp. nov.) and highlight geographical sampling deficiencies, which, if addressed with additional fieldwork, should lead to additional new species discoveries. Due to the difficulty of identifying non-overlapping differences in scalation on similarly sized, small-bodied skinks, species level diversity in diminutive Philippine forest skinks is undoubtedly substantially underestimated.